2002
DOI: 10.1002/app.10806
|View full text |Cite
|
Sign up to set email alerts
|

Graft reaction of acrylic acid onto metallocene‐based polyethylene‐octene elastomer

Abstract: ABSTRACT:In this study, grafting of acrylic acid (AA) onto metallocene-based polyethylene-octene elastomer (POE) was investigated by using benzoyl peroxide as an initiator. Grafted product was characterized by using Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, X-ray diffraction spectroscopy, and differential scanning calorimetry (DSC). Both the grafting percentage and the gel yield, at equilibrium, were higher for POE containing lower degree of comonomer conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…The new peaks at 1716 and 1732 cm Ϫ1 in the purified sample that have been attributed to carbonyl group (CAO) stretch vibration of grafted AA and grafted MMA were qualitative evidence of grafting in the melt. 8,26 The peak area of the coarse sample was higher than that of purified sample for each graft system, indicating that the homopolymerization has occurred during grafting process. Figure 3 shows the 1 H NMR spectra of LLDPE, purified LLDPE-g-AA, and LLDPE-g-MMA.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The new peaks at 1716 and 1732 cm Ϫ1 in the purified sample that have been attributed to carbonyl group (CAO) stretch vibration of grafted AA and grafted MMA were qualitative evidence of grafting in the melt. 8,26 The peak area of the coarse sample was higher than that of purified sample for each graft system, indicating that the homopolymerization has occurred during grafting process. Figure 3 shows the 1 H NMR spectra of LLDPE, purified LLDPE-g-AA, and LLDPE-g-MMA.…”
mentioning
confidence: 85%
“…The appearance of peaks is due to AA grafted onto the main or branch chain of LLDPE skeleton. 26 The resonance of the ␣-methylene OCH 2 (OOH) protons is not observed, suggesting that the chain transfer reaction is not dominant termination mode. By comparing the integral of the resonance of the ␣-methine OCH(OOH)O protons at 2.35 ppm with that of the methylene OCH 2 O protons at 1.0 -1.6 ppm, the average number of AA units per 10 4 carbon backbone is estimated to be 1.7, which is consistent with the results obtained by FTIR.…”
mentioning
confidence: 94%
“…Therefore, we think there is only physical dispersion between starch and PHB for the PHB/starch blend because extra new carbon peaks cannot be observed in the 13 C-NMR spectrum. As the result of our previous work [26], it was found that the 13 C-NMR spectrum of POE-g-AA had some extra peaks (C β = 35.63 ppm; C α = 42.19 ppm; -C=O, δ = 175.05 ppm) caused by grafting of AA onto POE. A comparison of signals for PHB/starch and PHB-g-AA/starch ( Fig.…”
Section: Ft-ir Analysismentioning
confidence: 72%
“…4A and 4B shows that, in addition to the original peaks of the unmodified PHB, some peaks appeared (4, δ = 1.8-2.0 ppm; 5, δ = 2.2-2.4 ppm) in the 1 H-NMR spectrum of PHB-g-AA. The extra peaks 4 and 5 may be due to the reason that AA was grafted onto the main or branch chain of PHB skeleton because they indicated the functional group of AA [23,26]. Therefore, from the results of FT-IR and 1 H-NMR, it is proven that AA was indeed grafted onto PHB.…”
Section: Ft-ir Analysismentioning
confidence: 94%
“…In this way, these copolymers have been used in modifying polar polymer. Functional monomers that have been widely used in the modification mainly include maleic anhydride, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] acrylic acids, 17,18 glycidyl methacrylate, 19 silane 20 and undecylenic Acid. 21 Such modifications are generally aimed at obtaining single monomer grafts or short length grafts that substantially change the polymer's chemical or reactive properties but not the mechanical properties.…”
mentioning
confidence: 99%